Realtime monitoring on the HIT photovoltaic module characteristic parameters at STC, high and low irradiance conditions in Algeria - Benlebna, Soumia; Kumar, Nallapaneni Manoj; Tahri, Ali (Elsevier, 2018)
This paper deals with the study on 233 Wp HIT PV module characteristics that defines its performance and operation. The chosen HIT PV module is exposed to outdoor conditions at Saida City of Algeria. The module is tested in high irradiance and low irradiance situations that were recorded over a specific year. Based on the monitored data in these two situations, its performance characteristics were evaluated and compared with standard test condition parameters. From the results it is observed that, irradiance variation effects the HIT PV module characteristics. The variation in maximum power extracted, efficiency, and fill factor were observed. Apart from this weather parameters like ambient temperature, module temperature, wind speed, and relative humidity had also influenced the performance characteristics of HIT PV module.